The Synthesis of Zinc Oxide (ZnO) Nanoparticles Using Extract Tomato (Solanum lycopersicum) As Capping Agent and Its Antioxidant Activity - Demi Dama Yanti; Glory Angelina; Arif Ashari; Ahmad Anggraria Jaya Agung; Aditya Ayuwulanda (Department of Chemistry - Universitas Bangka Belitung, 2024)
Zinc oxide (ZnO) nanoparticles are one of the most widely studied nanoparticles for various applications and other alternatives because of their unique properties. The uniqueness of these properties depends on the technique used to synthesize ZnO nanoparticles. This study aims to synthesize ZnO nanoparticles using tomato crude extract as a capping agent and to analyze the antioxidant activity of ZnO nanoparticles using DPPH and ascorbic acid as standard solutions. The synthesized powder of ZnO nanoparticles was characterized using XRD and SEM. The results obtained for the crystal size of the capping agent and without the capping agent were 20.597 nm and 24.717 nm according to JCPDS No. 00-036-1451. The particle size of ZnO using tomato extract as a capping agent is 43.325 nm which indicates that the particles are in the nanosize range and are spherical in shape. The IC50 yield of ZnO nanoparticles using a capping agent was 133.9623 ppm which indicated that ZnO nanoparticles had moderate antioxidant activity.